Anti-desmoglein2 autoantibodies are present in patients with cardiac sarcoidosis and correlate with cardiac inflammation. (24th May 2021) - Suna, G; Kolios, A; Chatterjee, D; Fatah, M; Gasperetti, A; Casella, M; Sommariva, E; Franzen, D; Manka, R; Pazhenkottil, A; Ruschitzka, F; Boyman, O; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): The Zurich ACM Program is supported by generous grants from the Georg and Bertha Schwyzer-Winniker Foundation, the Baugarten Foundation, Swiss National Science Foundation, Swiss Heart Foundation and Wild Foundation. This work is also supported by a Canadian Institutes of Health Research grant (FRN: 162402) and the Labatt Heart Centre and Waugh Family Innovation Funds, Caitlin Elizabeth Morris Memorial Fund, Alex Corrance Memorial Foundation and Meredith Cartwright. BACKGROUND Arrhythmogenic right ventricular cardiomyopathy (ARVC) has several phenocopies such as cardiac sarcoidosis (CS), idiopathic outflow tract ventricular tachycardia (OT-VT) and myocarditis. Differentiation between these entities can be challenging. Recently, we have identified diagnostic anti-desmoglein-2 autoantibodies (anti-DSG2 Abs) in patients with ARVC. PURPOSE We sought to examine whether anti-DSG2 Abs are also present in clinical phenocopies of ARVC. METHODS Anti-DSG2 Abs in sera of 25, 19 and 22 patients with sarcoidosis, OT-VT and myocarditis, respectively, were assessed by western blots and ELISA. Clinical and imaging parameters, as well as conventional biomarkers were correlated to detected anti-DSG2 Ab intensity levels. RESULTS Anti-DSG2 Abs, at various intensities, were identified in 6/25 (24%) patients with sarcoidosis, all presenting with CS, but were absent in patients with OT-VT and myocarditis. Cardiac 18F- fluorodeoxyglucose positron emission tomography (18F-FDG PET) was positive in all sarcoidosis patients with positive anti-DSG2 Abs, corresponding to a median PET maximum standardized uptake value (SUVmax) of 5.65 [IQR: 5.15 – 10.9]. In sarcoidosis patients without anti-DSG2 Abs, the SUVmax values were significantly lower with a median of 0 [IQR: 0 – 4] (p = 0.011). The Pearson correlation coefficient (R) was 0.188 (p = 0.039) indicating a positive correlation between cardiac 18F-FDG uptake and anti-DSG2 Abs. No significant correlation was detected for any of the other clinical parameters and biomarkers. CONCLUSIONS In addition to being present in ARVC, anti-DSG2 Abs are also found in CS, a common phenocopy of ARVC; conversely, anti-DSG2 Abs are absent in idiopathic OT-VT and myocarditis. Anti-DSG2 Ab levels positively correlate with myocardial disease activity in CS as indicated by cardiac 18F-FDG PET scanning.